Quantitative study on toppling deformation zoning of antidip rock slope under different soft and hard rock conditions - Cai, Junchao; Liu, Jiangtao; Zhang, Jie; Wang, Junping; Zhang, Shuo; Qi, Guoqing (Frontiers in Earth Science, 2024)
Toppling deformation can be classified into deep toppling (DT) and shallow toppling (ST) based on deformation mechanisms and development depth of rock mass under different soft and hard rock conditions. Currently, the toppling zoning indicators and quantitative criteria are not uniform, and human factors have a significant influence on the toppling zoning indicators. Summerizing and analyzing the existing toppling cases and toppling zoning researches, this study selects rock layer toppled angle, maximum tension within layer, unit tension within layer, and longitudinal wave velocity as indicators for toppling zoning. Considering the differences in the characteristics of deep toppling (DT) and shallow toppling (ST), the quantitative criteria for the deep and shallow toppling zoning indicators are determined respectively. This study employs the Analytic Hierarchy Process (AHP) and fuzzy comprehensive evaluation method to establish toppling zoning evaluation models. The deep toppling dam site slope at Miaowei hydropower station and the shallow toppling bank slope of Xingguang Ⅲ formation at Xiluodu Hydropower Station were tested, respectively. These results are compared with toppling zoning of field surveys to verify the rationality and applicability of the models. This achievement holds significant reference value for the toppling zoning of rock masses in engineering slopes, especially in the construction, development, and engineering management of toppling slopes.